Influence of water application on photosynthesis, growth and biomass characteristics in Jatropha curcas - Verma, Krishan K; Vatsal, Shweta; Gupta, Ramwant K; Ranjan, Sanjay; Verma, Chhedi Lal; Singh, Munna (Current Botany, 2012)
The effect of CO2 assimilation, stomatal conductance, transpiration rate, water use efficiency, growth and biomass productivity were studied in Jatropha curcas under different moisture levels of water (100, 75, 50 and 25% of field capacity). CO2 assimilation, stomatal conductance, transpiration, growth and biomass were reduced in response to decreasing moisture content of water. The decreased CO2 assimilation during irrigation stress was found largely dependent on stomatal closure, which reduced available internal CO2 concentration and restricted water loss through transpiration based on leaf gas exchange hypothesis linked with stomatal limitation for photosynthesis to reduce carbon uptake followed by loss in leaf area expansion which declined total carbon uptake, growth and biomass in Jatropha curcas seedlings.